2022
DOI: 10.1039/d1cy01688a
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments of Co3O4-based materials as catalysts for the oxygen evolution reaction

Abstract: The demand for the development of clean and efficient energy is becoming more and more pressing due to depleting fossil fuels and environmental concerns. Hydrogen is a high energy density...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 163 publications
0
27
0
Order By: Relevance
“…A close CV observation shows an oxidation peak at ∼1.52 V, which can be ascribed to the reconstructed Co 4+ species on the surface of Co 9 S 8 /Co 3 O 4 . The Raman spectrum of Co 9 S 8 /Co 3 O 4 after the CV cycling test shows a broad peak at 576 cm –1 (Figure S19), suggesting the presence of CoO 2 species. , The peaks at 610 and 472 cm –1 can be ascribed to Co 3 O 4 and Co 9 S 8 , respectively. , For Co 3 O 4 , Co/Co 3 O 4 , and Co 9 S 8 , the CV cycling curves show a bit of a shift, indicating a less stable structure of these catalysts (Figure S20a,d,g). The peaks at 1.47 and 1.37 V corresponding to the oxidation of Co from Co 2+ /Co 3+ and Co 3+ /Co 4+ can be observed in the CV cycling curves, suggesting the in situ formation of CoOOH and Co 4+ species on the surface of Co 3 O 4 and Co/Co 3 O 4 , respectively. , CV curves of Co 9 S 8 exhibit anodic peaks at 1.15 and 1.37 V due to the oxidation of Co + to Co 2+ and Co 2+ to Co 3+ , respectively.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A close CV observation shows an oxidation peak at ∼1.52 V, which can be ascribed to the reconstructed Co 4+ species on the surface of Co 9 S 8 /Co 3 O 4 . The Raman spectrum of Co 9 S 8 /Co 3 O 4 after the CV cycling test shows a broad peak at 576 cm –1 (Figure S19), suggesting the presence of CoO 2 species. , The peaks at 610 and 472 cm –1 can be ascribed to Co 3 O 4 and Co 9 S 8 , respectively. , For Co 3 O 4 , Co/Co 3 O 4 , and Co 9 S 8 , the CV cycling curves show a bit of a shift, indicating a less stable structure of these catalysts (Figure S20a,d,g). The peaks at 1.47 and 1.37 V corresponding to the oxidation of Co from Co 2+ /Co 3+ and Co 3+ /Co 4+ can be observed in the CV cycling curves, suggesting the in situ formation of CoOOH and Co 4+ species on the surface of Co 3 O 4 and Co/Co 3 O 4 , respectively. , CV curves of Co 9 S 8 exhibit anodic peaks at 1.15 and 1.37 V due to the oxidation of Co + to Co 2+ and Co 2+ to Co 3+ , respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Meanwhile, transition-metal-based compounds, especially the group VIII 3d metals of Fe, Co, and Ni, are attractive as nonprecious metal catalysts for the electrochemical water oxidation reaction due to their low cost, abundant resources, high activity, long-term durability, and excellent electronic properties. For example, Zhang et al fabricated a series of hierarchical Co 3 O 4 hollow nanoplates doped with different metal atoms and found that Fe-doped Co 3 O 4 exhibited superior electrocatalytic properties for OER with an overpotential of 262 mV at 10 mA cm –2 . Wang et al synthesized single-atomic-Mo-dispersed Co 9 S 8 nanoflakes and the advanced catalyst exhibited pronounced water oxidation activities in universal pH conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Co 3 O 4 NPs (61 mV/dec.) [ 37 , 38 ], reflecting the faster kinetic of s -Co 3 O 4 NPs. On the other hand, cm -Co 3 O 4 showed a higher Tafel slope of 67.6 mV/dec.…”
Section: Resultsmentioning
confidence: 99%
“…have been investigated and great progress has been made. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In both acidic and alkaline electrolysis systems, the first elementary step of the HER is the Volmer reaction. The second step is the Heyrovsky or Tafel reaction and the intermediates involved are slightly different.…”
Section: Introductionmentioning
confidence: 99%